Prawda sądowa i powoływanie się na fakty w postępowaniu cywilnym: [Judical truth and adducing facts in civil procedure] (Studia Prawnicze / The Legal Studies, 1985)
The article deals with theoretical problems connected with the principle of adducing controversial facts in a given case by the parties. According to the principle it is assumed that only the parties have a right to establish facts on which the decision is to be based and, as a consequence, the judge cannot know and take into account facts which, being even indispensable for passing the decision, have not been clearly adducted by the party. The author considers problems connected with this principle referring to the question of objective truth and classification of facts.It turns out that a restrictive effect of the principle, as far as seeking judicial truth is concerned, is effective olny when adducing the fact is a precise and full definition of a legal fact assumed as a basis of the claim. Thus, formal notion of judicial truth as truth dependent only on facts adduced by the parties may not be considered a general definition of judicial truth. The author doubts if such notion can be supported at all.